Pemanfaatan Thermoelectric Generator (TEG) untuk Penyimpanan Energi Panas dari Limbah Industri - Sukendar, Tateng; Utsman, Fajar; Sinambela, Rismen (JURNAL TEKNIK INDUSTRI, 2025)
The increase in industrial activity in Indonesia has resulted in a large volume of waste heat that is often discarded without being utilized. One promising solution to convert this waste heat into electrical energy is the use of a Thermoelectric Generator (TEG). This study examines the utilization of the TEG type SP1848-27145 to harness industrial waste heat within a temperature range of 150–250 °C, as well as to evaluate the potential of the generated energy for storage applications. The utilization of industrial waste heat energy is an efficient strategy to support clean energy transition and industrial sustainability. This study aims to analyze the potential of TEG type SP1848-27145 in storing heat energy from industrial waste within a temperature range of 150–250 °C.